Shedding Light on the Dynamic Role of the “Target of Rapamycin” Kinase in the Fast-Growing C4 Species Setaria viridis, a Suitable Model for Biomass Crops - da Silva, Viviane Cristina Heinzen; Martins, Marina C. M.; Calderan-Rodrigues, Maria Juliana; Artins, Anthony; Monte Bello, Carolina Cassano; Gupta, Saurabh; Sobreira, Tiago J. P.; Riaño-Pachón, Diego Mauricio; Mafra, Valéria; Caldana, Camila (Frontiers in Plant Science, 2021)
The Target of Rapamycin (TOR) kinase pathway integrates energy and nutrient availability into metabolism promoting growth in eukaryotes. The overall higher efficiency on nutrient use translated into faster growth rates in C4 grass plants led to the investigation of differential transcriptional and metabolic responses to short-term chemical TOR complex (TORC) suppression in the model Setaria viridis. In addition to previously described responses to TORC inhibition (i.e., general growth arrest, translational repression, and primary metabolism reprogramming) in Arabidopsis thaliana (C3), the magnitude of changes was smaller in S. viridis, particularly regarding nutrient use efficiency and C allocation and partitioning that promote biosynthetic growth. Besides photosynthetic differences, S. viridis and A. thaliana present several specificities that classify them into distinct lineages, which also contribute to the observed alterations mediated by TOR. Indeed, cell wall metabolism seems to be distinctly regulated according to each cell wall type, as synthesis of non-pectic polysaccharides were affected in S. viridis, whilst assembly and structure in A. thaliana. Our results indicate that the metabolic network needed to achieve faster growth seems to be less stringently controlled by TORC in S. viridis.